An experimental study on the oscillation of the propagating syngas-air flame in a duct. (18th June 2021) - Yu, Minggao; Qi, Beibei; Yang, Xufeng; Han, Shixin
Abstract: In this paper, premixed syngas-air flame propagating from the open end to the closed end were experimentally investigated. The effects of equivalence ratios, 0.8 ≤ Ф ≤ 1.2, and hydrogen volume fractions, 10% ≤ α (H2 ) ≤ 90%, on flame deformation and oscillation had been discussed in detail. The tulip-like flame was observed because of the large pressure gradient. Results indicate that the pressure wave plays an important role in the flame deformation and oscillation. The flame oscillates as hydrogen volume fraction varies. There are two oscillation modes. When the flame oscillates as mode Ⅰ, the flame first oscillates smoothly, then the oscillation is gradually enhanced, and finally the oscillation decays. The interaction of flame and pressure waves continuously stimulates the flame deformation and oscillation, finally the violent flame folding emerges in the later stage. When the flame oscillates as mode Ⅱ, the flame just oscillates violently in the early stage. Highlights: Flame propagating from the open end to the closed end was experimentally studied. Violent flame deformation and oscillation were observed. The flame oscillation was divided into two modes as the hydrogen fraction increases. Pressure wave was responsible for flame deformation and oscillation.